2020
DOI: 10.1111/pbi.13483
|View full text |Cite
|
Sign up to set email alerts
|

The genome of Cleistogenes songorica provides a blueprint for functional dissection of dimorphic flower differentiation and drought adaptability

Abstract: Summary Cleistogenes songorica (2n = 4x = 40) is a desert grass with a unique dimorphic flowering mechanism and an ability to survive extreme drought. Little is known about the genetics underlying drought tolerance and its reproductive adaptability. Here, we sequenced and assembled a high‐quality chromosome‐level C. songorica genome (contig N50 = 21.28 Mb). Complete assemblies of all telomeres, and of ten chromosomes were derived. C. songorica underwent a recent tetraploidization (~19 million years ago) and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 99 publications
2
42
0
Order By: Relevance
“…In this study, a total of 50 Dof genes were identified in the C. songorica genome database [ 41 ]. For convenience, these C. songorica Dof genes were named CsDof01 - CsDof50 ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, a total of 50 Dof genes were identified in the C. songorica genome database [ 41 ]. For convenience, these C. songorica Dof genes were named CsDof01 - CsDof50 ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The TBtools software was used to draft the CsDof chromosomal location map to show the distribution of each CsDof gene on the C. songorica chromosome ( Figure 2 ). Referring to the previous study [ 41 ], the 20 chromosome of heterotetraploid C. songorica genome were divided into 2 subgenomes ( Table S1 ). The results showed that 46 of the 50 CsDof genes were located on the 20 chromosomes; however, 4 members ( CsDof45 , CsDof46 , CsDof47 , and CsDof50 ), which were anchored on the scaffolds, could not be located on any C. songorica chromosomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-quality reads, poly-N sequences from the raw data and reads containing adapters were removed to generate clean reads. Furthermore, HISAT2 software was used to map the clean reads to the C. songorica genome [4,54], and StringTie (1.3.1) was used to quantify the gene expression levels according to the fragments per kilobase of transcript per million fragments (FPKM) method [55]. DEGs were analysed by the DESeq R package.…”
Section: Illumina Rna-seq Library Construction and Sequencingmentioning
confidence: 99%
“…Therefore, it is important to determine the genomic, transcriptomic and physiological mechanisms of heat tolerance in plants, which are of great importance to accelerate crops and forages breeding aiming at thermotolerance improvement. Cleistogenes songorica, a C4 plant, is a desert grass that distributed widely in the wild lands in the northwest part of China [4]. C. songorica can grow in semi-arid, arid and desert regions where the annual rainfall ranges from 100 to150 mm.…”
Section: Introductionmentioning
confidence: 99%